Electromagnetic waveguides theory and applications - Mahmoud, S. F. (Institution of Engineering and Technology, 1991)
This book has six chapters and deals with guided electromagnetic waves; closed waveguides; waveguides with constant impedance walls; open waveguides; low crosspolar waveguides; and guided waves in subsurface tunnels. The appendices on generalized orthogonal coordinate system and cylindrical wave functions are also given.